Organic photoelectric conversion element

JP7643229B2Active Publication Date: 2025-03-11MITSUBISHI CHEM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021121623
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-26
Publication Date
2025-03-11
Estimated Expiration
2041-07-26

AI Technical Summary

Benefits of technology

【0023】 本発明によれば、ある程度の耐熱性(例えば、ガラス転移温度Tg:100~160℃)が期待できる汎用的な熱硬化成分の加熱硬化物よりなる架橋構造を光電変換層内に形成することで、当該熱硬化成分の加熱硬化物の耐熱性よりも高い耐熱性を示す有機光電変換素子を提供することができ、有機光電変換素子について、効率的な耐熱性の改善を行うことができ、高温環境下でも光電変換特性の低下の少ない有機光電変換素子を提供することができる。 有機物のみで光電変換層に高耐熱性(例えば、200℃以上)を付与する事は通常困難である。本発明では、ある程度の耐熱性が期待できる汎用的な熱硬化成分を用い(このような材料は数多くあり、添加剤選択の自由度が高い·適材適所の添加剤選択ができる)、かつ「架橋構造」を用いることで、材料そのものから期待される耐熱性以上の高耐熱性を付与することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643229000012
    Figure 0007643229000012
  • Figure 0007643229000013
    Figure 0007643229000013
  • Figure 0007643229000001
    Figure 0007643229000001
Patent Text Reader

Abstract

To provide an organic photoelectric conversion element in which bridge structure formed from the heat-hardened product of a thermosetting component is formed in a photoelectric conversion layer, which therefore exhibits a heat resistance higher than that of the heat-hardened product of the thermosetting component.SOLUTION: An organic photoelectric conversion element is provided which has a photoelectric conversion layer having p-type and n-type organic semiconductors. Bridge structure formed from a heat-hardened product of a thermosetting component is formed in the photoelectric conversion layer. In the organic photoelectric conversion element, a heat resistance temperature T calculated by specific heat resistance evaluation is higher than a glass transition temperature Tg of the heat-hardened product of the thermosetting component.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an organic photoelectric conversion element having a photoelectric conversion layer containing a p-type organic semiconductor and an n-type organic semiconductor. [Background technology]

[0002] Photoelectric conversion elements such as organic solar cells and organic photodetectors require heat resistance to withstand the heating environment during the reflow process during element manufacturing. However, these elements generally do not have sufficient heat resistance to withstand the heating environment expected during manufacturing, and this insufficient heat resistance may lead to a deterioration of the photoelectric conversion characteristics. One of the reasons for the deterioration of the photoelectric conversion characteristics is thought to be as follows. That is, the phase separation structure (compatibility between p-type organic semiconductor and n-type organic semiconductor) of the bulk heterojunction (BHJ) type photoelectric conversion layer consisting of p-type organic semiconductor and n-type organic semiconductor plays an important role in the photoelectric conversion characteristics, but this phase separation structure does not have sufficient stability against heat. For this reason, the phase separation structure changes in a high-temperature environment. This is because the p-type organic semiconductor and n-type organic semiconductor in the photoelectric conversion layer flow under high-temperature conditions, and the p-type organic semiconductors and the n-type organic semiconductors partially aggregate with each other, damaging the bulk heterojunction between the p-type organic semiconductor and the n-type organic semiconductor. Therefore, various studies have been conducted to improve the heat resistance of the photoelectric conversion layer and the heat stability of the phase-separated structure.

[0003] For example, Non-Patent Document 1 discloses that the heat resistance of a photoelectric conversion element can be improved by introducing a crosslinked structure into a photoelectric conversion layer using a p-type semiconductor into which a crosslinking group has been introduced. Non-Patent Document 2 describes the use of P3HT (poly(3-hexylthiophene)) and PC 61 BM ([6,6]-phenyl-C 61It has been shown that the heat resistance of the photoelectric conversion layer can be improved by adding the thermally crosslinkable monomer OBOCO (octane-1,8-diylbis(1,4-dihydrobenzo[d][1,2]oxathiine-6-carboxylate-3-oxide)) to an active layer made of octane-1,8-diylbis(1,4-dihydrobenzo[d][1,2]oxathiine-6-carboxylate-3-oxide) and thermally curing the photoelectric conversion layer. Non-Patent Document 3 discloses that the heat resistance of a photoelectric conversion layer made of PM6 and BTTT-2Cl is improved by adding an n-type semiconductor PZ1 to the photoelectric conversion layer.

[0004] [ka]

[0005] In Patent Document 1, a photoelectric conversion element that maintains good photoelectric conversion characteristics even after a heat resistance test at 150 to 220° C. for 50 minutes has been successfully developed by using a specific semiconductor material. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Materials.Today.2015,18,425-435 [Non-Patent Document 2] J.Mater.Chem.A,2013,1,4589-4594 [Non-Patent Document 3] Nat.Commun.2020,11,1218 [Patent documents]

[0007] [Patent Document 1] Patent Publication No. 2021-057573 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the techniques of the above Non-Patent Documents 1 to 3 all have the following problems. The methods described in Non-Patent Documents 1 and 3 require the development of a new organic semiconductor having a crosslinking group. Furthermore, a fullerene derivative is essential for the curing reaction of the thermosetting monomer OBOCO in Non-Patent Document 2, and when this method is used, there are limitations on the selection of the semiconductor material for the photoelectric conversion layer. The method described in Patent Document 1 requires the use of a specific semiconductor material that is highly heat-resistant, and is therefore not very versatile in that there are limitations on the selection of semiconductor materials.

[0009] In view of these problems of the prior art, a general-purpose system that can impart heat resistance by the post-addition of additives, etc., regardless of the selection of semiconductor material, is ideal. Furthermore, when considering imparting heat resistance by stabilizing the phase separation structure of the photoelectric conversion layer, a system that forms a crosslinked structure in the photoelectric conversion layer is effective. In other words, if the additive itself, which is blended separately from the p-type organic semiconductor and the n-type organic semiconductor, can form a crosslinked structure in the photoelectric conversion layer to improve its heat resistance, the semiconductor material can be selected with a high degree of freedom and can be easily applied to existing combinations of p-type organic semiconductors and n-type organic semiconductors. Furthermore, considering the effect on the semiconductor material responsible for photoelectric conversion, it is desirable that the curing reaction proceeds with heat rather than light. In addition, if a wide variety of versatile thermosetting components that can be expected to have a certain degree of heat resistance (for example, glass transition temperature Tg: 100 to 160°C) can be selected as an additive, it is useful in terms of the versatility of the method. Furthermore, if a photoelectric conversion layer having a higher heat resistance than that of the crosslinked structure formed in the photoelectric conversion layer can be formed by the method, it is useful in terms of the improvement effect of high heat resistance. However, the reality is that no technology that satisfies these requirements has been reported.

[0010] The present invention aims to provide an organic photoelectric conversion element that exhibits higher heat resistance than the heat resistance of a heat-cured product of a thermosetting component by forming a cross-linked structure consisting of a heat-cured product of the thermosetting component in a photoelectric conversion layer. [Means for solving the problem]

[0011] As a result of intensive research aimed at solving the above problems, the inventors have discovered a technology that can impart to an organic photoelectric conversion element heat resistance higher than the heat resistance of a heat-cured product of a thermosetting component that constitutes a cross-linked structure formed in a photoelectric conversion layer.

[0012] The present invention has been achieved based on these findings, and has the following gist.

[0013] [1] An organic photoelectric conversion element having a photoelectric conversion layer including a p-type organic semiconductor and an n-type organic semiconductor, a crosslinked structure made of a heat-cured product of a thermosetting component is formed in the photoelectric conversion layer, The organic photoelectric conversion element is characterized in that a heat-resistant temperature T defined below is higher than a glass transition temperature Tg of a heat-cured product of the thermosetting component. <Definition of heat resistance temperature T> The highest test temperature in the heat resistance test at which the external quantum efficiency maintenance rate calculated by the following formula using the external quantum efficiency EQE1 value measured for the organic photoelectric conversion element after a heat resistance test in which the element is held at a predetermined test temperature for 50 minutes and the external quantum efficiency EQE0 value measured for the organic photoelectric conversion element without conducting the heat resistance test is 85% or more is defined as the heat resistance temperature T of the organic photoelectric conversion element. External quantum efficiency maintenance rate = (EQE1 / EQE0) x 100

[0014] [2] The organic photoelectric conversion element according to [1], wherein the heat resistant temperature T is 200° C. or higher, and the glass transition temperature Tg of the heat-cured product of the thermosetting component is 40° C. or higher lower than the heat resistant temperature T.

[0015] [3] The organic photoelectric conversion element according to [1] or [2], wherein the p-type organic semiconductor is a non-crosslinkable p-type organic semiconductor, and the n-type organic semiconductor is a non-crosslinkable n-type organic semiconductor.

[0016] [4] The organic photoelectric conversion element according to any one of [1] to [3], wherein the thermosetting component contains an epoxy resin as a main component.

[0017] [5] The organic photoelectric conversion element according to [4], wherein the thermosetting component further contains a curing agent.

[0018] [6] The organic photoelectric conversion element according to any one of [1] to [5], wherein the curing temperature of the thermosetting component is within the range of 100 to 220° C.

[0019] [7] The organic photoelectric conversion element according to any one of [1] to [6], wherein the p-type organic semiconductor is a conjugated polymer, and the n-type organic semiconductor is a semiconductor not containing a fullerene skeleton.

[0020] [8] The organic photoelectric conversion element according to [7], wherein the n-type organic semiconductor comprises a compound represented by the following formula (I) and / or a polymer of two or more compounds represented by the following formula (I):

[0021] [ka]

[0022] (In the above formula (I), A represents an atom selected from Group 14 of the periodic table, and X 1 ~X 4 R each independently represents a hydrogen atom or a halogen atom. 1a ,R 1b each independently represents a linear or branched alkyl group; R 2 ~R 5 each independently represents a linear or branched alkyl group, a linear or branched alkoxy group, a linear or branched thioalkyl group, or a hydrogen atom. Effect of the Invention

[0023] According to the present invention, by forming a crosslinked structure consisting of a heat-cured product of a general-purpose thermosetting component that can be expected to have a certain degree of heat resistance (for example, glass transition temperature Tg: 100 to 160°C) in a photoelectric conversion layer, it is possible to provide an organic photoelectric conversion element that exhibits higher heat resistance than the heat resistance of the heat-cured product of the thermosetting component. This makes it possible to efficiently improve the heat resistance of the organic photoelectric conversion element, and to provide an organic photoelectric conversion element that exhibits little deterioration in photoelectric conversion characteristics even in a high-temperature environment. It is usually difficult to impart high heat resistance (e.g., 200°C or higher) to a photoelectric conversion layer using only organic matter. In the present invention, a general-purpose thermosetting component that can be expected to have a certain degree of heat resistance is used (there are many such materials, and there is a high degree of freedom in the selection of additives; additives can be selected according to the right material and place), and a "crosslinked structure" is used, thereby making it possible to impart high heat resistance beyond that expected from the material itself. [Brief description of the drawings]

[0024] [Figure 1] 1A and 1B are schematic diagrams for explaining the mechanism of improvement of heat resistance according to the present invention, in which (a) shows a conventional method and (b) shows the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating an example of an embodiment of an organic photoelectric conversion element of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The following describes in detail the form for carrying out the present invention. However, the following description of the constituent elements is a representative example of an embodiment of the present invention, and the present invention is not limited to these contents.

[0026] [Organic photoelectric conversion element] The organic photoelectric conversion element of the present invention is an organic photoelectric conversion element having a photoelectric conversion layer containing a p-type organic semiconductor and an n-type organic semiconductor, in which a crosslinked structure consisting of a heat-cured product of a thermosetting component is formed in the photoelectric conversion layer, and the organic photoelectric conversion element is characterized in that the heat-resistant temperature T defined below is higher than the glass transition temperature Tg of the heat-cured product of the thermosetting component. <Definition of heat resistance temperature T> The highest test temperature in the heat resistance test at which the external quantum efficiency maintenance rate calculated by the following formula using the external quantum efficiency EQE1 value measured for the organic photoelectric conversion element after a heat resistance test in which the element is held at a predetermined test temperature for 50 minutes and the external quantum efficiency EQE0 value measured for the organic photoelectric conversion element without conducting the heat resistance test is 85% or more is defined as the heat resistance temperature T of the organic photoelectric conversion element. External quantum efficiency maintenance rate = (EQE1 / EQE0) x 100

[0027] The external quantum efficiency of the organic photoelectric conversion element is measured by the method described in the Examples section below.

[0028] The organic photoelectric conversion element of the present invention has a heat-resistant temperature T of 100° C. or higher, preferably 140° C. or higher, more preferably 180° C. or higher, and particularly preferably 200° C. or higher. In addition, the glass transition temperature Tg of the heat-cured product of the thermosetting component formed in the photoelectric conversion layer is 5° C. or higher, preferably 10° C. or higher, more preferably 20° C. or higher, and particularly preferably 40° C. or higher than the heat-resistant temperature T. That is, T-Tg is preferably 5° C. or higher, more preferably 10° C. or higher, even more preferably 20° C. or higher, and particularly preferably 40° C. or higher. T of 100° C. or more is preferable in that it can be used in a variety of high-temperature environments. In addition, in terms of heat resistance that enables the element to withstand the heating environments expected in the manufacturing process, T is preferably 140° C. or more, more preferably 180° C. or more, and particularly preferably 200° C. or more.

[0029] Such an organic photoelectric conversion element of the present invention can be formed, for example, by using an organic semiconductor ink containing a p-type organic semiconductor, an n-type organic semiconductor, a thermosetting component and a solvent to form a photoelectric conversion layer, forming a film of this organic semiconductor ink by a wet film formation method on the surface on which the photoelectric conversion layer is to be formed (usually on the electrode surface of the organic photoelectric conversion element of the present invention described below, or on another layer such as a hole transport layer formed on the electrode), and then heat-curing the formed coating film. Here, the p-type organic semiconductor and n-type organic semiconductor used in the organic semiconductor ink of the present invention are preferably non-crosslinkable p-type organic semiconductor and non-crosslinkable n-type organic semiconductor, respectively. That is, if the organic semiconductor ink contains a thermosetting component, the thermosetting component itself in the organic semiconductor ink can form a crosslinked structure, so there is no need to introduce functional groups for crosslinking reactions into the p-type organic semiconductor or n-type organic semiconductor, or to design the molecules for crosslinking reactions. Therefore, non-crosslinkable p-type and n-type organic semiconductors can be used, which allows for a high degree of freedom in the selection of semiconductor materials and allows for easy application to existing combinations of p-type and n-type organic semiconductors.

[0030] Here, the term "thermosetting component" refers to a component that itself crosslinks and hardens due to heat to form a crosslinked structure. Moreover, the "non-crosslinkable" in "non-crosslinkable p-type organic semiconductor" means that the p-type organic semiconductor and the thermosetting component do not undergo a crosslinking reaction, and does not exclude the crosslinking, polymerization, or condensation reaction between p-type organic semiconductors. Similarly, the "non-crosslinkable" in "non-crosslinkable n-type organic semiconductor" means that the n-type organic semiconductor and the thermosetting component do not undergo a crosslinking reaction, and does not exclude the crosslinking, polymerization, or condensation reaction between n-type organic semiconductors. Moreover, the "non-crosslinkable" of these organic semiconductors does not exclude the crosslinking, polymerization, or condensation reaction between the "p-type organic semiconductor" and the "n-type organic semiconductor".

[0031] The organic photoelectric conversion element of the present invention will be described below by exemplifying an embodiment in which a photoelectric conversion layer (hereinafter, sometimes referred to as "the photoelectric conversion layer of the present invention") of an organic photoelectric conversion element of the present invention is formed using an organic semiconductor ink containing a non-crosslinkable p-type organic semiconductor, a non-crosslinkable n-type organic semiconductor, a thermosetting component, and a solvent (hereinafter, sometimes referred to as "the organic semiconductor ink of the present invention"). However, the method of forming the photoelectric conversion layer of the organic photoelectric conversion element of the present invention is not limited to the method using the organic semiconductor ink of the present invention, and any method can be used as long as it can obtain an organic photoelectric conversion element having a heat resistant temperature T higher than the glass transition temperature Tg of the heat-cured product of the thermosetting component that constitutes the crosslinked structure formed in the photoelectric conversion layer, as described above.

[0032] [Formation of photoelectric conversion layer using the organic semiconductor ink of the present invention] <Mechanism> The mechanism by which the organic semiconductor ink of the present invention improves the heat resistance of the photoelectric conversion layer will be described with reference to FIG. As shown in Figure 1(a), conventional organic semiconductor inks consist of a p-type organic semiconductor (a p-type polymer in Figure 1) and an n-type organic semiconductor (an n-type molecule in Figure 1) dissolved in a solvent. The p-type polymer and n-type molecules are compatible with each other in the photoelectric conversion layer formed by depositing this organic semiconductor ink, resulting in high photoelectric conversion efficiency. However, in conventional methods, when exposed to a high-temperature environment (for example, a heat resistance test at 150 to 220°C for 50 minutes), the p-type polymer and n-type molecules flow and aggregate, significantly reducing their compatibility, and the photoelectric conversion efficiency decreases as these molecules become partially localized.

[0033] In contrast, since the organic semiconductor ink of the present invention contains a thermosetting component, when this organic semiconductor ink is formed into a film and thermally cured, the thermosetting component forms a crosslinked structure in the formed photoelectric conversion layer. In the photoelectric conversion layer in which the crosslinked structure of the thermosetting component is formed in this way, even when exposed to a high-temperature environment (for example, a heat resistance test at 150 to 220°C for 50 minutes), the p-type polymer and n-type molecule are prevented from flowing due to the network of the crosslinked structure of the thermosetting component, and the compatibility between the two is hardly impaired, and therefore a decrease in photoelectric conversion efficiency is suppressed.

[0034] <Thermosetting component> The thermosetting component used in the present invention is not particularly limited as long as it can be cured by heating to form a network-like crosslinked structure in the photoelectric conversion layer such that the heat resistance temperature T>the glass transition temperature Tg, as described above.

[0035] From the viewpoint of easily forming a crosslinked structure effective for improving heat resistance that satisfies the condition of heat resistance temperature T>glass transition temperature Tg, the thermosetting component is preferably one that contains one or more of epoxy resin, phenol resin, melamine resin, urethane resin, silicone resin, etc. as a main component, and it is particularly preferable to use an epoxy resin. Note that the "main component" here refers to the component that is contained in the thermosetting component in the greatest amount, and the content of the main component in the thermosetting component is preferably 38 mass% or more, and particularly preferably 49 to 100 mass%.

[0036] When an epoxy resin is used as the thermosetting component, it is preferable to use a curing agent for the epoxy resin in combination. By using a curing agent in combination, the thermosetting can be promoted quickly.

[0037] (Epoxy resin) The epoxy resin is not particularly limited, and any epoxy resin generally known as such can be used.

[0038] Examples of epoxy resins that can be used include phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, and epoxy resins having a triphenylmethane skeleton. Novolak resins obtained by condensing or co-condensing phenols such as phenols including glycerol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, etc. and / or naphthols such as α-naphthol, β-naphthol, dihydroxynaphthalene, etc. with compounds having an aldehyde group such as formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, salicylaldehyde, etc. under an acidic catalyst, epoxidized novolak resins, diglycidyl ethers of bisphenol A, bisphenol F, bisphenol S, alkyl-substituted or unsubstituted biphenols, stilbene-type epoxy resins, hydroquinone-type epoxy resins, polybasic acids such as phthalic acid and dimer acid, etc. Examples of the epoxy resin include glycidyl ester type epoxy resins obtained by the reaction of epichlorohydrin with diaminodiphenylmethane, glycidylamine type epoxy resins obtained by the reaction of epichlorohydrin with polyamines such as diaminodiphenylmethane and isocyanuric acid, epoxidized products of co-condensed resins of dicyclopentadiene and phenols, epoxy resins having a naphthalene ring, phenol aralkyl resins containing a xylylene skeleton or a biphenylene skeleton, epoxidized products of aralkyl type phenol resins such as naphthol aralkyl resins, trimethylolpropane type epoxy resins, terpene modified epoxy resins, linear aliphatic epoxy resins or alicyclic epoxy resins obtained by oxidizing olefin bonds with peracids such as peracetic acid, and sulfur atom-containing epoxy resins. These epoxy resins may be used alone or in combination of two or more.

[0039] Among these, novolac-type epoxy resins are preferred from the viewpoint of curability, dicyclopentadiene-type epoxy resins are preferred from the viewpoint of low moisture absorption, naphthalene-type epoxy resins and triphenylmethane-type epoxy resins are preferred from the viewpoint of heat resistance and low warpage, and biphenylene-type epoxy resins and naphthol aralkyl-type epoxy resins are preferred from the viewpoint of flame retardancy.

[0040] As the epoxy resin, it is preferable to use one with a small epoxy equivalent because it is easy to form a crosslinked structure that is effective in improving heat resistance in the photoelectric conversion layer by forming many crosslinking points of a network structure that can prevent the flow of p-type organic semiconductors and n-type organic semiconductors by heat curing, while it is preferable to use one with a large epoxy equivalent in terms of handling of the epoxy resin. From this viewpoint, the epoxy equivalent of the epoxy resin is preferably 50 to 1000 g / eq., more preferably 70 to 500 g / eq., and particularly preferably 90 to 300 g / eq. In the present invention, the term "epoxy equivalent" is defined as "the mass of an epoxy compound containing one equivalent of an epoxy group" and can be measured in accordance with JIS K7236.

[0041] These epoxy resins can be commercially available products. Examples of commercially available epoxy resins that can be used include jER825 (epoxy equivalent 175 g / eq), jER827 (epoxy equivalent 185 g / eq), jER828 (epoxy equivalent 189 g / eq), jER834 (epoxy equivalent 250 g / eq), jER806 (epoxy equivalent 165 g / eq), jER807 (epoxy equivalent 170 g / eq), jER604 (epoxy equivalent 120 g / eq), jER630 (epoxy equivalent 98 g / eq), jER1032H60 (epoxy equivalent 169 g / eq), and q), jER152 (epoxy equivalent 175g / eq), jER154 (epoxy equivalent 178g / eq), jER157S70 (epoxy equivalent 210g / eq), YX-7700 (epoxy equivalent 273g / eq), YX-8000 (epoxy equivalent 205g / eq), YX-8800 (epoxy equivalent 179g / eq), YX-4000 (epoxy equivalent 186g / eq), YX-7105 (epoxy equivalent 480g / eq), YX-7400 (epoxy equivalent 440g / eq) (all trade names, manufactured by Mitsubishi Chemical Corporation), YD-127 (epoxy equivalent 18 5g / eq), YD-128 (epoxy equivalent 189g / eq), YDF-170 (epoxy equivalent 170g / eq), YDPN-638 (epoxy equivalent 180g / eq), TX-0911 (epoxy equivalent 172g / eq) (all trade names, manufactured by Nippon Steel Sumikin Chemical & Material Co., Ltd.), EPICLON840 (epoxy equivalent 185g / eq), EPICLON850 (epoxy equivalent 189g / eq), EPICLON830 (epoxy equivalent 170g / eq), EPICLON835 (epoxy equivalent 172g / eq), HP-4032 (epoxy equivalent weight 150g / eq), HP-4700 (epoxy equivalent weight 162g / eq), HP-4770 (epoxy equivalent weight 204g / eq), HP-4750 (epoxy equivalent weight 185g / eq), HP-7200 (epoxy equivalent weight 265g / eq), N-730A (epoxy equivalent weight 174g / eq), N-740 (epoxy equivalent weight 181g / eq), N-770 (epoxy equivalent weight 187g / eq), TSR-400 (epoxy equivalent weight 338g / eq) (all trade names, manufactured by DIC Corporation), GAN (epoxy equivalent weight 125g / eq), GOT (epoxy equivalent weight 135g / eq),Examples of the epoxy equivalent include NC-2000 (epoxy equivalent 241 g / eq), NC-3000 (epoxy equivalent 275 g / eq) (all trade names, manufactured by Nippon Kayaku Co., Ltd.), MY-0500 (epoxy equivalent 110 g / eq), MY-0600 (epoxy equivalent 106 g / eq), ECN-1299 (epoxy equivalent 230 g / eq) (all trade names, manufactured by Huntsman Japan Co., Ltd.), DER331, DER354 (epoxy equivalent 170 g / eq) (epoxy equivalent 187 / eq), and DER332 (epoxy equivalent 173 g / eq) (all trade names, manufactured by The Dow Chemical Company), but are not limited thereto.

[0042] The content of such epoxy resin in the thermosetting component is preferably 38 to 100 mass%, more preferably 49 to 99.5 mass%, and particularly preferably 75 to 99.5 mass%. If the content of the epoxy resin in the thermosetting component is equal to or higher than the lower limit, the epoxy resin can efficiently form a crosslinked structure effective for improving heat resistance. If the content of the epoxy resin in the thermosetting component is equal to or lower than the upper limit, the content of the co-component components such as the curing agent shown below can be ensured, and the curing reaction can be smoothly promoted.

[0043] (hardening agent) In the present invention, a curing agent refers to a substance that contributes to the crosslinking reaction and / or chain extension reaction between epoxy groups of an epoxy resin. In the present invention, even substances that are usually called "curing accelerators" or "curing catalysts" are considered to be curing agents as long as they contribute to the crosslinking reaction and / or chain extension reaction between epoxy groups of an epoxy resin.

[0044] The curing agent is not particularly limited, and any agent generally known as an epoxy resin curing agent can be used, such as phenol-based curing agents, amine-based curing agents such as aliphatic amines, polyether amines, alicyclic amines, and aromatic amines, acid anhydride-based curing agents, amide-based curing agents, tertiary amines, and imidazoles.

[0045] Among these, from the viewpoint of heat resistance, etc., it is preferable to include a phenol-based curing agent, an acid anhydride-based curing agent, or an amide-based curing agent. In addition, it is also preferable to use imidazoles from the viewpoint of sufficiently progressing the curing reaction and improving heat resistance. The curing agent may be used alone or in combination of two or more kinds.

[0046] <Phenol-based hardener> Specific examples of phenol-based hardeners include various polyhydric phenols such as bisphenol A, bisphenol F, bisphenol S, bisphenol AD, hydroquinone, resorcin, methylresorcin, biphenol, tetramethylbiphenol, dihydroxynaphthalene, dihydroxydiphenyl ether, thiodiphenols, phenol novolac resins, cresol novolac resins, phenol aralkyl resins, biphenyl aralkyl resins, naphthol aralkyl resins, terpene phenol resins, dicyclopentadiene phenol resins, bisphenol A novolac resins, trisphenol methane type resins, naphthol novolac resins, brominated bisphenol A, and brominated phenol novolac resins. Examples of such phenol resins include polyhydric phenol resins obtained by the condensation reaction of phenols with various aldehydes such as benzaldehyde, hydroxybenzaldehyde, crotonaldehyde, and glyoxal, polyhydric phenol resins obtained by the condensation reaction of xylene resin and phenols, co-condensation resins of heavy oils or pitches with phenols and formaldehydes, phenol-benzaldehyde-xylylene dimethoxide polycondensates, phenol-benzaldehyde-xylylene dihalide polycondensates, phenol-benzaldehyde-4,4'-dimethoxide biphenyl polycondensates, and phenol-benzaldehyde-4,4'-dihalide biphenyl polycondensates.

[0047] These phenol-based curing agents may be used alone or in any combination of two or more kinds in any blend ratio.

[0048] The amount of the phenol-based curing agent is preferably 0.1 to 1000 parts by mass, more preferably 500 parts by mass or less, further preferably 300 parts by mass or less, and particularly preferably 100 parts by mass or less, based on 100 parts by mass of the epoxy resin.

[0049] <Amine-based hardener> Examples of amine-based curing agents (excluding tertiary amines) include aliphatic amines, polyether amines, alicyclic amines, and aromatic amines.

[0050] Examples of aliphatic amines include ethylenediamine, 1,3-diaminopropane, 1,4-diaminopropane, hexamethylenediamine, 2,5-dimethylhexamethylenediamine, trimethylhexamethylenediamine, diethylenetriamine, iminobispropylamine, bis(hexamethylene)triamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, N-hydroxyethylethylenediamine, and tetra(hydroxyethyl)ethylenediamine.

[0051] Examples of polyetheramines include triethylene glycol diamine, tetraethylene glycol diamine, diethylene glycol bis(propylamine), polyoxypropylene diamine, polyoxypropylene triamines, and the like.

[0052] Examples of alicyclic amines include isophoronediamine, methacenediamine, N-aminoethylpiperazine, bis(4-amino-3-methyldicyclohexyl)methane, bis(aminomethyl)cyclohexane, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraoxaspiro(5,5)undecane, and norbornenediamine.

[0053] Examples of aromatic amines include tetrachloro-p-xylylenediamine, m-xylylenediamine, p-xylylenediamine, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, 2,4-diaminoanisole, 2,4-toluenediamine, 2,4-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-diamino-1,2-diphenylethane, 2,4-diaminodiphenylsulfone, 4,4'-diaminodiphenylsulfone, m-aminophenol, m-aminobenzylamine, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, triethanolamine, methylbenzylamine, α-(m-aminophenyl)ethylamine, α-(p-aminophenyl)ethylamine, diaminodiethyldimethyldiphenylmethane, and α,α'-bis(4-aminophenyl)-p-diisopropylbenzene.

[0054] The amine-based curing agents listed above may be used alone or in any combination of two or more in any blend ratio.

[0055] The amine-based curing agent is preferably used so that the equivalent ratio of the functional groups in the curing agent to the epoxy groups in the epoxy resin is in the range of 0.8 to 1.5, since within this range, unreacted epoxy groups and functional groups of the curing agent are less likely to remain.

[0056] Examples of tertiary amines include 1,8-diazabicyclo(5,4,0)undecene-7, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol.

[0057] The tertiary amines listed above may be used alone or in any combination of two or more kinds in any blend ratio.

[0058] The above tertiary amine is preferably used so that the equivalent ratio of the functional group in the curing agent to the epoxy group in the epoxy resin is in the range of 0.8 to 1.5. This range is preferable because unreacted epoxy groups and functional groups of the curing agent are less likely to remain.

[0059] <Acid anhydride curing agent> Examples of the acid anhydride-based curing agent include acid anhydrides and modified products of acid anhydrides. Examples of acid anhydrides include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic anhydride, dodecenylsuccinic anhydride, polyadipic anhydride, polyazelaic anhydride, polysebacic anhydride, poly(ethyloctadecanedioic) anhydride, poly(phenylhexadecanedioic) anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methylhimic anhydride, trialkyltetrahydrophthalic anhydride, Examples of the anhydride include methylcyclohexene dicarboxylic anhydride, methylcyclohexene tetracarboxylic anhydride, ethylene glycol bistrimellitate dianhydride, HET anhydride, nadic anhydride, methylnadic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexane-1,2-dicarboxylic anhydride, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic dianhydride, and 1-methyl-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic dianhydride.

[0060] The modified acid anhydride may be, for example, the above-mentioned acid anhydride modified with glycol. Examples of glycols that can be used for modification include alkylene glycols such as ethylene glycol, propylene glycol, and neopentyl glycol, and polyether glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol. Furthermore, copolymer polyether glycols of two or more of these glycols and / or polyether glycols may also be used.

[0061] In the modified acid anhydride, it is preferable to modify the acid anhydride with 0.4 moles or less of glycol per mole of acid anhydride. When the amount of modification is equal to or less than the upper limit, the viscosity of the epoxy resin composition does not become too high, and the workability tends to be good, and the rate of the curing reaction with the epoxy resin also tends to be good.

[0062] The acid anhydride curing agents listed above may be used alone or in any combination of two or more in any amount.

[0063] When an acid anhydride curing agent is used, it is preferable to use it so that the equivalent ratio of the functional group in the curing agent to the epoxy group in the epoxy resin is in the range of 0.8 to 1.5. If it is within this range, it is preferable because unreacted epoxy groups and functional groups of the curing agent are unlikely to remain.

[0064] <Amide-based hardener> Examples of the amide-based curing agent include dicyandiamide and its derivatives, polyamide resins, and the like. The amide-based curing agent may be used alone or in any combination and ratio of two or more kinds. When an amide-based curing agent is used, it is preferable to use the amide-based curing agent in an amount of 0.1 to 20 mass % based on the total amount of the epoxy resin and the amide-based curing agent.

[0065] <Imidazoles> Examples of imidazoles include 2-phenylimidazole, 2-ethyl-4(5)-methylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyano-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl- Examples of the imidazoles include 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and adducts of epoxy resins and the above imidazoles. Note that since imidazoles have catalytic activity, they can generally be classified as curing accelerators, but in the present invention, they are classified as curing agents.

[0066] The imidazoles listed above may be used alone or in any combination and ratio of two or more.

[0067] When an imidazole is used, it is preferable to use the imidazole in an amount of 0.1 to 20% by mass based on the total amount of the epoxy resin and the imidazole.

[0068] (Cure accelerator) The thermosetting component according to the present invention may contain a curing accelerator, which makes it possible to shorten the curing time and lower the curing temperature. The curing accelerator is not particularly limited, but specific examples include organic phosphines, phosphorus compounds such as phosphonium salts, tetraphenylboron salts, organic acid dihydrazides, boron halide amine complexes, and the like.

[0069] Phosphorus compounds that can be used as curing accelerators include triphenylphosphine, diphenyl(p-tolyl)phosphine, tris(alkylphenyl)phosphine, tris(alkoxyphenyl)phosphine, tris(alkyl alkoxyphenyl)phosphine, tris(dialkylphenyl)phosphine, tris(trialkylphenyl)phosphine, tris(tetraalkylphenyl)phosphine, tris(dialkoxyphenyl)phosphine, tris(trialkoxyphenyl)phosphine, tris(tetraalkoxyphenyl)phosphine, trialkylphosphine, Examples of such organic phosphines include organic phosphines such as phosphine, dialkylarylphosphine, and alkyldiarylphosphine; complexes of such organic phosphines with organic borons; and compounds obtained by adding such organic phosphines to quinone compounds such as maleic anhydride, 1,4-benzoquinone, 2,5-toluquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, and phenyl-1,4-benzoquinone, and compounds such as diazophenylmethane.

[0070] Among the above-listed curing accelerators, organic phosphines and phosphonium salts are preferred, and organic phosphines are most preferred. The curing accelerator may be one of the above-listed ones, or two or more of them may be mixed in any combination and ratio.

[0071] The curing accelerator is preferably used in a range of 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the epoxy resin. More preferably, it is 0.5 parts by mass or more, and even more preferably, it is 1 part by mass or more, and more preferably, it is 15 parts by mass or less, and even more preferably, it is 10 parts by mass or less. When the content ratio of the curing accelerator is equal to or more than the lower limit, a good curing acceleration effect can be obtained, and when the content ratio is equal to or less than the upper limit, it is preferable because the desired curing properties can be easily obtained.

[0072] (curing temperature) The thermosetting component used in the present invention preferably has a curing temperature within the range of 100 to 220°C. If the curing temperature is 100°C or higher, it is possible to prevent the thermosetting component from reacting in the ink when preparing the organic semiconductor ink. When the thermosetting component is cured by heating to form a crosslinked structure in the photoelectric conversion layer, a higher curing temperature is preferable. On the other hand, if the curing temperature is 220°C or lower, it is possible to prevent the p-type organic semiconductor and n-type organic semiconductor from flowing before the crosslinked structure is formed by curing due to excessive high temperature heating, which changes the phase separation structure and reduces the photoelectric conversion characteristics when the thermosetting component is cured by heating to form a crosslinked structure in the formation of the photoelectric conversion layer. From this viewpoint, the curing temperature of the thermosetting component is more preferably 120 to 220°C, and particularly preferably 140 to 220°C.

[0073] In order to set the curing temperature of the thermosetting component within the above range, techniques such as selecting an epoxy resin having an appropriate curing temperature and selecting an appropriate curing agent and curing accelerator and adjusting the blending ratios thereof may be adopted.

[0074] (Thermosetting component content) The content of the thermosetting component in the organic semiconductor ink of the present invention is preferably 1 to 100 parts by mass, more preferably 1 to 40 parts by mass, and particularly preferably 1 to 10 parts by mass, per 100 parts by mass of the total of the non-crosslinkable p-type organic semiconductor and the non-crosslinkable n-type organic semiconductor. When an epoxy resin is used as the thermosetting component, the content of the epoxy resin in the organic semiconductor ink of the present invention is preferably 1 to 100 parts by mass, more preferably 1 to 40 parts by mass, and particularly preferably 1 to 10 parts by mass, per 100 parts by mass of the total of the non-crosslinkable p-type organic semiconductor and the non-crosslinkable n-type organic semiconductor. The content ratio of the thermosetting component relative to the total of the p-type organic semiconductor and the n-type organic semiconductor in the organic semiconductor ink corresponds to the content ratio of the crosslinked structure consisting of the heat-cured product of the thermosetting component relative to the total of the p-type organic semiconductor and the n-type organic semiconductor in the photoelectric conversion layer of the present invention.

[0075] If the content ratio of the thermosetting component and the epoxy resin in the organic semiconductor ink is equal to or higher than the above lower limit, a crosslinked structure effective for improving heat resistance can be formed in a sufficient proportion in the photoelectric conversion layer. If the content ratio of the thermosetting component in the organic semiconductor ink is equal to or lower than the above upper limit, the content of the non-crosslinked p-type organic semiconductor and the non-crosslinked n-type organic semiconductor can be ensured, and a photoelectric conversion layer with excellent photoelectric conversion efficiency can be formed.

[0076] <Non-crosslinkable p-type organic semiconductor> The non-crosslinkable p-type organic semiconductor is not particularly limited and may be a known compound, but is preferably a donor semiconductor, typically an organic semiconductor (compound). For example, a hole-transporting organic compound that is a p-type conjugated polymer may be used, and a compound that is easily capable of donating electrons may be used. Specific examples of skeletons having excellent hole transport properties include a carbazole structure, a thiophene structure, a benzodithiophene structure, a thienothiophene structure, a dibenzofuran structure, a triarylamine structure, a naphthalene structure, a phenanthrene structure, and a pyrene structure. Among these, it is particularly preferable to use one that can be mixed with a non-crosslinkable n-type organic semiconductor described below and then coated to form a film.

[0077] Specifically, for example, the one represented by the following formula (II) is used: In formula (II), n is a positive number.

[0078] [ka]

[0079] In order to improve the characteristics as a p-type semiconductor, the non-crosslinkable p-type organic semiconductor used in the present invention preferably has a weight average molecular weight of 100,000 or more, more preferably 150,000 or more. From the viewpoint of solubility in a solvent, the upper limit is preferably 400,000 or less, more preferably 300,000 or less. Here, the weight average molecular weight of the non-crosslinkable p-type organic semiconductor is a value determined by size exclusion chromatography.

[0080] <Non-crosslinkable n-type organic semiconductor> An n-type semiconductor is an acceptor semiconductor, and is mainly represented by an electron transport compound, which is a compound that has the property of easily accepting electrons. More specifically, it refers to the compound with the larger electron affinity when two compounds are used in contact with each other. Therefore, any compound that has electron accepting properties can be used as an acceptor compound. For example, condensed aromatic carbocyclic compounds (naphthalene derivatives, anthracene derivatives, phenanthrene derivatives, tetracene derivatives, pyrene derivatives, perylene derivatives, fluoranthene derivatives), 5- to 7-membered heterocyclic compounds containing a nitrogen atom, an oxygen atom, or a sulfur atom (e.g., pyridine, pyrazine, pyrimidine, pyridazine, triazine, quinoline, quinoxaline, quinazoline, phthalazine, cinnoline, isoquinoline, pteridine, acridine, phenazine, phenanthroline, tetrazole, pyrazole, imidazole, thiazoline, Examples of suitable ligands include metal complexes having a ligand selected from the group consisting of aryl, oxazole, indazole, benzimidazole, benzotriazole, benzoxazole, benzothiazole, carbazole, purine, triazolopyridazine, triazolopyrimidine, tetrazaindene, oxadiazole, imidazopyridine, pyrazine, pyrrolopyridine, thiadiazolopyridine, dibenzazepine, and tribenzazepine, polyarylene compounds, fluorene compounds, cyclopentadiene compounds, silyl compounds, and nitrogen-containing heterocyclic compounds. However, as described above, any compound having a larger electron affinity than the compound used as the donor semiconductor may be used as the acceptor semiconductor.

[0081] When a fullerene skeleton is used as an n-type semiconductor, even if a bulk heterojunction structure is used to increase the photoelectric conversion efficiency, the presence of the bulky fullerene skeleton increases the distance between the n-type semiconductor and the p-type semiconductor, resulting in a decrease in the photoelectric conversion efficiency.

[0082] Therefore, in the non-crosslinkable p-type organic semiconductor of the present invention, the ratio of the n-type semiconductor having a fullerene skeleton to the n-type semiconductor not having a fullerene skeleton is preferably 10 mass % or less, and more preferably the n-type semiconductor is a fullerene skeleton-free semiconductor in which the n-type semiconductor does not substantially contain a fullerene skeleton. Here, "substantially free of fullerene skeleton" means that the non-fullerene n-type semiconductor is responsible for transporting electrons of the charges generated in the photoelectric conversion layer, and may contain a small amount to improve the morphology of the photoelectric conversion layer. For such a purpose, the n-type semiconductor containing a fullerene skeleton is usually contained in an amount of 5 mass% or less relative to the non-fullerene n-type semiconductor not having a fullerene skeleton, and this ratio is preferably 2 mass% or less.

[0083] The non-crosslinkable n-type organic semiconductor used in the present invention preferably contains a compound represented by the following formula (I) and / or a polymer of two or more compounds represented by the following formula (I), particularly from the viewpoints of compatibility with the non-crosslinkable p-type organic semiconductor and ability to form a (BHJ) type photoelectric conversion layer.

[0084] [ka]

[0085] (In the above formula (I), A represents an atom selected from Group 14 of the periodic table, and X 1 ~X 4 R each independently represents a hydrogen atom or a halogen atom. 1a ,R 1b each independently represents a linear or branched alkyl group; R 2 ~R 5 each independently represents a linear or branched alkyl group, a linear or branched alkoxy group, a linear or branched thioalkyl group, or a hydrogen atom.

[0086] In the above formula (I), A is preferably a carbon atom or a silicon atom. X 1 ~X 4are each independently a hydrogen atom or a halogen atom, and the halogen atom is preferably a fluorine atom or a chlorine atom. R 1a ,R 1b are each independently a straight-chain or branched alkyl group, and the alkyl group preferably has 8 to 24 carbon atoms, particularly 10 to 20 carbon atoms, and even more preferably 12 to 18 carbon atoms.

[0087] Examples of the linear or branched alkyl group having 8 to 24 carbon atoms include linear alkyl groups such as n-octyl, n-decyl, lauryl, myristyl, palmityl, and stearyl groups, primary branched alkyl groups such as 2-ethylhexyl and 2-butyloctyl groups, and secondary alkyl groups such as 2-octyl, 2-nonyl, and 2-decyl groups. Of these, linear alkyl groups or primary branched alkyl groups are preferred, and 2-ethylhexyl or 2-butyloctyl groups are particularly preferred.

[0088] R 2 ~R 5 are each independently a linear or branched alkyl group, a linear or branched alkoxy group, a linear or branched thioalkyl group, or a hydrogen atom, and the alkyl group, alkoxy group, and thioalkyl group preferably have 8 to 24 carbon atoms, particularly 10 to 20 carbon atoms, and even more particularly 12 to 18 carbon atoms. R 2 ~R 5 is preferably each independently an alkoxy group having 8 to 24 carbon atoms, and specific examples thereof include a 2-ethylhexyloxy group or a palmityloxy group.

[0089] From the viewpoint of compatibility with non-crosslinkable p-type organic semiconductors and ability to form BHJ-type photoelectric conversion layers, 1a and R 1b are preferably the same group, and R 2 ~R 5 is preferably composed of two or more different groups.

[0090] <Contents of non-crosslinkable p-type organic semiconductor and non-crosslinkable n-type organic semiconductor> The ratio of the non-crosslinked p-type organic semiconductor to the non-crosslinked n-type organic semiconductor contained in the organic semiconductor ink of the present invention is preferably 0.5 to 2.5 times, particularly 1.0 to 2.0 times, in terms of the mass ratio of the non-crosslinked n-type organic semiconductor to the non-crosslinked p-type organic semiconductor (n-type organic semiconductor / p-type organic semiconductor mass ratio). If the amount of the non-crosslinked n-type organic semiconductor is more than the above range and the amount of the non-crosslinked p-type organic semiconductor is less than the above range, the sensitivity in the near infrared region tends to decrease. Conversely, if the amount of the non-crosslinked p-type organic semiconductor is more than the above range and the amount of the non-crosslinked n-type organic semiconductor is less than the above range, dark current tends to be generated easily. The content ratio of the p-type organic semiconductor and the n-type organic semiconductor in the organic semiconductor ink corresponds to the content ratio of the p-type organic semiconductor and the n-type organic semiconductor in the photoelectric conversion layer of the present invention.

[0091] <Solvent> The solvent contained in the organic semiconductor ink of the present invention may be any solvent capable of dissolving the non-crosslinkable p-type organic semiconductor, the non-crosslinkable n-type organic semiconductor, and the thermosetting component, and examples thereof include aromatic solvents such as aromatic hydrocarbon solvents such as toluene, xylene, mesitylene, and cyclohexylbenzene, aromatic halogen-containing solvents such as chlorobenzene and o-dichlorobenzene, aliphatic halogen-containing solvents such as 1,2-dichloroethane, and aliphatic ethers such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol-1-monomethyl ether acetate (PGMEA). Examples of the solvent include ether-based solvents such as aromatic ethers such as phenyl acetate, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, anisole, phenetole, 2-methoxytoluene, 3-methoxytoluene, 4-methoxytoluene, 2,3-dimethylanisole, and 2,4-dimethylanisole; aliphatic ester-based solvents such as ethyl acetate, n-butyl acetate, ethyl lactate, and n-butyl lactate; and ester-based solvents such as aromatic esters such as phenyl acetate, phenyl propionate, methyl benzoate, ethyl benzoate, isopropyl benzoate, propyl benzoate, and n-butyl benzoate. These may be used alone or in combination of two or more.

[0092] Among these solvents, aromatic solvents are preferred from the viewpoint of the solubility of the non-crosslinked p-type organic semiconductor and the non-crosslinked p-type organic semiconductor, and aromatic halogen-containing solvents are particularly preferred.

[0093] <Other ingredients> The organic semiconductor ink of the present invention may contain, in addition to the above-mentioned thermosetting component, non-crosslinkable p-type organic semiconductor, non-crosslinkable n-type organic semiconductor and solvent, a stabilizer, a thickener and the like as necessary. However, when the organic semiconductor ink of the present invention contains these other components, in order to fully obtain the inherent effects of the organic semiconductor ink, it is preferable that the content of the other components in the organic semiconductor ink is 10 mass % or less relative to the total of the thermosetting component, non-crosslinkable p-type organic semiconductor, non-crosslinkable n-type organic semiconductor and other components.

[0094] <Solid content concentration> The solids concentration of the organic semiconductor ink of the present invention, i.e., the total content of the thermosetting components excluding the solvent in the organic semiconductor ink, the non-crosslinkable p-type organic semiconductor, the non-crosslinkable n-type organic semiconductor and other components contained as necessary, is preferably 10 to 30 mg / mL, and more preferably 12 to 24 mg / mL. When the solids concentration of the organic semiconductor ink is equal to or higher than the lower limit, the efficiency of forming the photoelectric conversion layer is excellent, whereas when the solids concentration is equal to or lower than the upper limit, the organic semiconductor ink can be easily prepared and is easy to handle.

[0095] <Method of manufacturing organic semiconductor ink> The organic semiconductor ink of the present invention can be produced by adding and mixing the above-mentioned thermosetting component, non-crosslinkable p-type organic semiconductor, non-crosslinkable n-type organic semiconductor, and other components contained as necessary to a solvent to obtain a predetermined concentration. In this case, the order in which the components are added is not particularly limited.

[0096] <Method of forming photoelectric conversion layer> The photoelectric conversion layer of the present invention can be formed by forming a film of the organic semiconductor ink of the present invention by a wet film formation method on a surface on which a photoelectric conversion layer is to be formed (usually on the electrode surface of the organic photoelectric conversion element of the present invention described below, or on another layer such as a hole transport layer formed on the electrode), and then heat-curing the formed coating film.

[0097] The wet film-forming method is not particularly limited, but specifically includes spin-coating. In this case, the conditions of spin-coating may be appropriately determined according to a standard method, taking into consideration the viscosity of the organic semiconductor ink, etc. The temperature during film-forming is also not particularly limited, but is a temperature at which the curing of the thermosetting component does not proceed, and is usually 100°C or less, for example, about 20 to 80°C.

[0098] The heating conditions for heat curing the formed coating film are those at which the thermosetting component can cure to form a crosslinked structure, and vary depending on the type of thermosetting component. The heating conditions are preferably the above-mentioned suitable curing temperature conditions, i.e., 100 to 220°C, more preferably 120 to 220°C, and particularly preferably 140 to 220°C, although these conditions vary depending on the type of thermosetting component. The heating time may also be any time that allows the thermosetting component to harden and form a crosslinked structure, and although it varies depending on the type of thermosetting component and the heating temperature, it is usually about 1 to 60 minutes.

[0099] The thickness of the photoelectric conversion layer of the present invention thus formed can be arbitrarily designed depending on the configuration of the photoelectric conversion layer and the application of the organic photoelectric conversion element. However, if the thickness is too thin, the light absorption is insufficient and the efficiency decreases, whereas if the thickness is too thick, the internal resistance increases and the loss becomes large. Therefore, the thickness is usually about 10 nm to 1 μm.

[0100] [Structure of organic photoelectric conversion element] The structure of the organic photoelectric conversion element of the present invention can be, for example, referred to in the description of JP-A-2007-324587, and is not particularly limited. For example, the organic photoelectric conversion element may have a structure in which a transparent electrode, an electron transport layer, a photoelectric conversion layer, a hole transport layer, and a metal electrode are laminated in this order on a transparent substrate, or may have a structure in which a transparent electrode, a hole transport layer, a photoelectric conversion layer, an electron transport layer, and a metal electrode are laminated in this order on a transparent substrate.

[0101] 1 is a schematic cross-sectional view showing an example of an organic photoelectric conversion element of the present invention. In this organic photoelectric conversion element 10, a first electrode 11, a hole transport layer 12, a photoelectric conversion layer 13, an electron transport layer 14, and a second electrode 15 as a lower electrode are laminated in this order. The hole transport layer 12, the photoelectric conversion layer 13, and the electron transport layer 14 form an organic photoelectric film 20. Usually, a substrate is provided on the side of the first electrode 11 opposite to the hole transport layer 12.

[0102] <Substrate> The organic photoelectric conversion element may include a substrate for supporting the first electrode, the hole transport layer, the photoelectric conversion layer, the electron transport layer, the second electrode, etc. The substrate may be provided on either the first electrode side or the second electrode side, or on both sides, but is preferably provided at least on the first electrode side. The substrate can be made of any material, but if light is incident from the substrate side, it must be made of a highly transparent material.

[0103] Examples of materials constituting the substrate include inorganic materials such as glass, sapphire, and titania; organic materials such as polyethylene terephthalate, polyethylene naphthalate, polyethersulfone, polyimide, nylon, polystyrene, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, fluororesin, vinyl chloride, polyethylene, cellulose, polyvinylidene chloride, aramid, polyphenylene sulfide, polyurethane, polycarbonate, polyarylate, and polynorbornene; paper materials such as paper and synthetic paper; composite materials such as metals such as stainless steel, titanium, and aluminum whose surfaces are coated or laminated to provide insulation; etc. The substrate may be made of one material alone, or two or more materials may be used in any combination and ratio.

[0104] Furthermore, there is no limitation on the shape and dimensions of the substrate, and they can be set arbitrarily. Furthermore, another layer may be laminated on the substrate in order to impart gas barrier properties or control the surface condition.

[0105] The thickness of the substrate can be arbitrarily designed depending on the application, constituent materials, etc. of the organic photoelectric conversion element. However, if it is too thin, it will lack strength and will not function as a support member, whereas if it is too thick, costs will increase. Therefore, the substrate is usually in the form of a film or plate having a thickness of about 10 μm to 50 mm.

[0106] <Electrode> The electrodes (first electrode, second electrode) can be made of any material having electrical conductivity.

[0107] Examples of materials constituting the electrodes include metals such as platinum, gold, silver, aluminum, chromium, nickel, copper, titanium, magnesium, calcium, barium, and sodium, or alloys thereof; metal oxides such as indium oxide and tin oxide, or composite oxides thereof (e.g., ITO, IZO); conductive polymers such as polyaniline, polypyrrole, polythiophene, and polyacetylene; conductive polymers to which dopants such as acids such as hydrochloric acid, sulfuric acid, and sulfonic acid, Lewis acids such as FeCl3, halogen atoms such as iodine, and metal atoms such as sodium and potassium have been added; conductive composite materials in which conductive particles such as metal particles, carbon black, fullerene, and carbon nanotubes are dispersed in a matrix such as a polymer binder. The materials constituting the electrodes may be used alone or in any combination and ratio of two or more.

[0108] In an organic photoelectric conversion element, at least one pair (two electrodes) is provided, and a photoelectric conversion layer is provided between the pair of electrodes. In this case, it is preferable that at least one of the pair of electrodes is transparent (i.e., transmits light absorbed by the photoelectric conversion layer for power generation). Examples of transparent electrode materials include complex oxides such as indium tin oxide (ITO) and indium zinc oxide (IZO); thin metal films, etc. In this case, there is no specific limit to the range of light transmittance, but considering the photoelectric conversion efficiency of the organic photoelectric conversion element, it is preferable that it is 80% or more. The light transmittance can be measured by a normal spectrophotometer.

[0109] The electrode has a function of collecting holes and electrons generated in the photoelectric conversion layer. Therefore, it is preferable to use a material suitable for collecting holes and electrons among the above-mentioned materials as the material of the electrode. Examples of electrode materials suitable for collecting holes include materials having a high work function such as Au and ITO. On the other hand, examples of electrode materials suitable for collecting electrons include materials having a low work function such as Al.

[0110] There is no particular limit to the thickness of the electrodes, and it is determined appropriately taking into consideration the material used and the required electrical conductivity, transparency, and the like, but it is usually about 10 nm to 100 μm.

[0111] The method for forming the electrodes is not limited, and they can be formed by a dry process such as vacuum deposition or sputtering. They can also be formed by a wet process using a conductive ink or the like. In this case, any conductive ink can be used, such as a conductive polymer or a metal particle dispersion. Furthermore, the electrodes may be laminated in two or more layers, and may be subjected to a surface treatment to improve the characteristics (electrical characteristics, wettability, etc.).

[0112] <Hole transport layer> A known hole transport material can be used for the hole transport layer. Specific examples of hole transport polymers include polytriarylamine compounds as exemplified below. Other examples include 2,7-bis(4-bromophenyl)-9,9-dihexylfluorene, 2-amino-9,9-dihexylfluorene, and polytolylarylamine compounds synthesized from 4-(4-(1,1-bis(4'-bromo-[1,1'-biphenyl]-4-yl)ethyl)phenyl)-1,2-dihydrocyclobuta[a]naphthalene, 4,4'-dibromobiphenyl, and 2-amino-9 Polytriarylamine compounds synthesized from 4,4'-dibromobiphenyl, 4-(3,5-dibromophenyl)-1,2-dihydrocyclobuta[a]naphthalene, and 2-amino-9,9-dihexylfluorene can be used, but are not limited to these.

[0113] [ka]

[0114] [ka]

[0115] [ka]

[0116] The method for forming the hole transport layer is not particularly limited, but it is preferably formed by a wet film formation method using a hole transporting polymer. In forming the hole transport layer by the wet film formation method, a composition for forming the hole transport layer containing a hole transporting polymer and a solvent is used.

[0117] The solvent is sufficient if it dissolves the hole transport polymer, and is usually a solvent that dissolves the hole transport polymer at room temperature in an amount of 0.05% by mass or more, preferably 0.5% by mass or more, and more preferably 1% by mass or more. The solvent is not particularly limited, but for example, ether solvents, ester solvents, aromatic hydrocarbon solvents, amide solvents, etc. are preferred.

[0118] Examples of the ether solvent include aliphatic ethers such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol-1-monomethyl ether acetate (PGMEA), and aromatic ethers such as 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, anisole, phenetole, 2-methoxytoluene, 3-methoxytoluene, 4-methoxytoluene, 2,3-dimethylanisole, and 2,4-dimethylanisole.

[0119] Examples of the ester solvent include aromatic esters such as phenyl acetate, phenyl propionate, methyl benzoate, ethyl benzoate, propyl benzoate, and n-butyl benzoate. Examples of aromatic hydrocarbon solvents include toluene, xylene, cyclohexylbenzene, 3-isopropylbiphenyl, 1,2,3,4-tetramethylbenzene, 1,4-diisopropylbenzene, cyclohexylbenzene, and methylnaphthalene. Examples of amide solvents include N,N-dimethylformamide, N,N-dimethylacetamide, etc. In addition to these, dimethyl sulfoxide, etc. can also be used.

[0120] The concentration of the hole transport polymer in the composition for forming the hole transport layer is arbitrary as long as it does not significantly impair the effects of the present invention, and a lower concentration is preferable in terms of uniformity of the film thickness, while a higher concentration is preferable in terms of preventing defects from occurring in the hole transport layer. Specifically, the concentration is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and particularly preferably 0.5% by mass or more, while the concentration is preferably 70% by mass or less, more preferably 60% by mass or less, and particularly preferably 50% by mass or less.

[0121] The concentration of the solvent in the composition for forming a hole transport layer is usually 10% by mass or more, preferably 30% by mass or more, and more preferably 50% by mass or more.

[0122] When forming a hole transport layer using the composition for forming a hole transport layer, the composition for forming a hole transport layer is usually heated after coating. The heating method is not particularly limited, but the conditions for drying by heating are usually 100°C or higher, preferably 120°C or higher, more preferably 150°C or higher, and usually 400°C or lower, preferably 350°C or lower, more preferably 300°C or lower. The heating time is usually 1 minute or more, preferably 24 hours or less. The heating means is not particularly limited, but means such as placing the laminate having the formed layer on a hot plate or heating in an oven can be used. For example, conditions such as heating on a hot plate at 120°C or more for 1 minute or more can be used.

[0123] The thickness of the hole transport layer is in one embodiment 50 nm or more and 100 nm or less, and in another embodiment, more than 100 nm or more and 400 nm or less, preferably 350 nm or less, that is, 50 nm or more and 400 nm or less, preferably 350 nm or less. When the thickness of the hole transport layer is equal to or greater than the lower limit, the effect of reducing dark current due to the provision of the hole transport layer as a blocking layer can be effectively obtained. When the thickness of the hole transport layer is equal to or less than the upper limit, the angle of incidence of light can be made wider in a CMOS image sensor using an organic photoelectric conversion element, and the organic photoelectric conversion element can be made thinner.

[0124] In order to effectively reduce dark current, the hole transport layer preferably has a LUMO shallower than the n-type organic semiconductor of the photoelectric conversion layer by 0.3 eV or more, more preferably has a LUMO shallower than the n-type organic semiconductor of the photoelectric conversion layer by 0.5 eV or more, and more preferably has a LUMO shallower than the n-type organic semiconductor of the photoelectric conversion layer by 1.0 eV or more. In addition, since the hole transport layer plays a role of efficiently transporting holes generated in the photoelectric conversion layer to the first electrode, the difference in HOMO between the hole transport layer and the p-type organic semiconductor of the photoelectric conversion layer is preferably within 0.5 eV, and more preferably within 0.3 eV.

[0125] <Photoelectric conversion layer> The photoelectric conversion layer is a layer that absorbs light and separates charges, and the photoelectric conversion layer of the organic photoelectric conversion element of the present invention is preferably the photoelectric conversion layer of the present invention formed from the organic semiconductor ink of the present invention.

[0126] <Electron transport layer> An electron transport layer is not necessarily required for an organic photoelectric conversion element. However, by providing an electron transport layer between the photoelectric conversion layer and the second electrode, it is possible to increase the photoelectric conversion efficiency and reduce the dark current.

[0127] The electron transport layer is formed from a compound capable of efficiently transporting electrons generated in the photoelectric conversion layer to the second electrode. The electron transporting compound used in the electron transport layer must have a high efficiency of electron injection from the photoelectric conversion layer and a high electron mobility, so that the injected electrons can be efficiently transported. For this reason, the difference in LUMO between the electron transport layer and the n-type semiconductor of the photoelectric conversion layer is preferably 1.5 eV or less, and more preferably 1.0 eV. In addition, when dark current is reduced by the electron transport layer, the electron transport layer preferably has a HOMO that is 0.3 eV or more deeper than the p-type semiconductor of the photoelectric conversion layer, more preferably has a HOMO that is 0.5 eV or more deeper, and even more preferably has a HOMO that is 1.0 eV or more deeper.

[0128] Examples of the electron transporting compound used in the electron transport layer include metal complexes such as aluminum complex of 8-hydroxyquinoline (JP-A-59-194393), metal complexes of 10-hydroxybenzo[h]quinoline, oxadiazole derivatives, distyrylbiphenyl derivatives, silole derivatives, 3-hydroxyflavone metal complexes, 5-hydroxyflavone metal complexes, benzoxazole metal complexes, benzothiazole metal complexes, trisbenzimidazolylbenzene (U.S. Pat. No. 5,645,948), quinoxaline compounds (JP-A-6-207169), phenanthroline derivatives (JP-A-5-331459), 2-t-butyl-9,10-N,N'-dicyanoanthraquinone diimine, n-type hydrogenated amorphous silicon carbide, n-type zinc sulfide, and n-type zinc selenide.

[0129] Furthermore, metal oxides such as titanium oxide, zinc oxide, tin oxide, cerium oxide, etc. can also be used as materials for forming the electron transport layer. In this case, the method for forming the electron transport layer can include a method of wet-forming nanoparticles of the metal oxide and drying them to form a metal oxide layer, or a method of wet-forming a precursor and converting it by heating.

[0130] The thickness of the electron transport layer is usually 1 nm or more, preferably 5 nm or more, and on the other hand, usually 300 nm or less, preferably 100 nm or less.

[0131] The electron transport layer can be formed by a wet film-forming method or a vacuum deposition method, but the vacuum deposition method is usually used.

[0132] <Other constituent layers> The organic photoelectric conversion element may include constituent layers other than the above-mentioned substrate, first and second electrodes, hole transport layer, photoelectric conversion layer and electron transport layer, so long as the effects of the present invention are not significantly impaired. For example, the organic photoelectric conversion element may be provided with a protective film to cover the photoelectric conversion layer portion and further the electrode portion in order to minimize the influence of the outside air. The protective layer may be composed of, for example, a polymer film such as a styrene resin, an epoxy resin, an acrylic resin, a polyurethane, a polyimide, a polyvinyl alcohol, a polyvinylidene fluoride, a polyethylene-polyvinyl alcohol copolymer, or the like; an inorganic oxide film or a nitride film such as silicon oxide, silicon nitride, or aluminum oxide; or a laminated film thereof.

[0133] There is no limitation on the method for forming the protective film. For example, when the protective film is a polymer film, a forming method by coating and drying a polymer solution, a forming method by coating or vapor-depositing a monomer and polymerizing it, etc. can be mentioned. In addition, when forming a polymer film, it is also possible to perform a crosslinking process or form a multi-layer film. On the other hand, when the protective film is an inorganic film such as an inorganic oxide film or a nitride film, for example, a forming method by a vacuum process such as a sputtering method or a vapor deposition method, or a forming method by a solution process represented by a sol-gel method can be used.

[0134] In order to allow the electrode to efficiently collect the charges generated in the photoelectric conversion layer, a charge injection layer may be provided between the first electrode and the hole transport layer, or between the electron transport layer and the second electrode. Furthermore, the organic photoelectric conversion element may be provided with an optical filter that does not transmit, for example, ultraviolet light on the light incident side. Since ultraviolet light generally accelerates the deterioration of an organic photoelectric conversion element, blocking this ultraviolet light can extend the life of the organic photoelectric conversion element.

[0135] <Method of Manufacturing Organic Photoelectric Conversion Element> An organic photoelectric conversion element is usually manufactured by laminating a first electrode, a hole transport layer, a photoelectric conversion layer, and a second electrode on a substrate in this order by the above-mentioned method, and a step of forming an electron transport layer, etc., which is provided between these layers as necessary, is provided.

[0136] <Applications of organic photoelectric conversion elements> The photoelectric conversion element of this embodiment is used in an optical sensor, an image sensor, etc. In this case, the optical sensor and the image sensor may have known configurations. EXAMPLES

[0137] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to the following examples.

[0138] <Measurement method> -How to measure film thickness The film thickness can be measured using, for example, a stylus surface profile evaluation device Dektak150 (manufactured by ULVAC, Inc.) as a contact type, or a non-contact type, for example, a profile measuring laser microscope VK-X200 (manufactured by Keyence Corporation). External quantum efficiency measurement method: The spectral sensitivity was measured using a solar simulator and electrical property measuring device (manufactured by Bunkoukeiki Co., Ltd.) to obtain the external quantum efficiency when a voltage of -5 V was applied to the element for light with a wavelength of 940 nm.

[0139] <Example 1> A transparent conductive film of indium tin oxide (ITO) was patterned on a glass substrate as an electrode. The surface of the ITO substrate was treated with an ultraviolet ozone cleaner (NL-UV253, manufactured by Japan Laser Electronics Co., Ltd.) for 10 minutes, and then a hole transport layer was formed as follows.

[0140] A composition for forming a hole transport layer was prepared by dissolving 60 mg of a polytriarylamine compound (hole transport polymer) represented by the following formula (1) in 1 mL of anisole. This composition was spin-coated on the electrode surface of an ITO substrate at a rotation speed of 1000 rpm for 60 seconds, and then heated and dried at 240°C for 30 minutes to form a hole transport layer with a thickness of 300 nm.

[0141] [ka]

[0142] An organic semiconductor ink was prepared by dissolving the following materials in a solvent: a non-crosslinkable p-type organic semiconductor, a non-crosslinkable n-type organic semiconductor, an epoxy resin, and a curing agent. Non-crosslinkable p-type organic semiconductor: p-type organic semiconductor represented by the above formula (II) (weight average molecular weight: 240,000) Non-crosslinkable n-type organic semiconductor: In the above formula (I), A = carbon atom X 1 ~X 4 = Chlorine atom R 1a ,R 1b = 2-ethylhexyl group R 2 = 2-ethylhexyl group R 3 = 2-ethylhexyloxy group R 4 ,R 5 = Hydrogen atom An n-type organic semiconductor compound Epoxy resin: an epoxy resin represented by the following formula (2) (manufactured by Mitsubishi Chemical Corporation) jER828 (epoxy equivalent: 189g / eq)

[0143] [ka]

[0144] Hardener: 2-ethyl-4-methylimidazole Solvent: Chlorobenzene

[0145] The mass ratio of the non-crosslinkable p-type organic semiconductor to the non-crosslinkable n-type organic semiconductor in the organic semiconductor ink (n-type organic semiconductor / p-type organic semiconductor) was 1.2, the content of the thermosetting component per 100 parts by mass combined of the non-crosslinkable p-type organic semiconductor and the non-crosslinkable n-type organic semiconductor was 5.25 parts by mass (the content of the epoxy resin was 5 parts by mass, and the content of the curing agent was 0.25 parts by mass), and the solids concentration of the organic semiconductor ink was 16.5 mg / mL.

[0146] This organic semiconductor ink was spin-coated onto the hole transport layer at 1,000 revolutions per minute, and then heated at 200°C for 30 minutes to harden the epoxy resin, forming a photoelectric conversion layer with a thickness of 150 nm.

[0147] Next, a 40 nm thick film of C60 fullerene (manufactured by Frontier Carbon Corp.) as an electron transport material and a 100 nm thick film of aluminum as a metal electrode were formed in a vacuum to obtain an organic photoelectric conversion element.

[0148] In addition, the epoxy resin (jER828 manufactured by Mitsubishi Chemical Corporation) used as the thermosetting component in this example and 2-ethyl-4-methylimidazole were obtained from a mixture containing 5 parts by mass of epoxy resin and 0.25 parts by mass of 2-ethyl-4-methylimidazole in the same manner as described above. The glass transition temperature Tg of the thermoset product was measured by differential scanning calorimetry and was found to be 160°C.

[0149] <Comparative Example 1> An organic photoelectric conversion element was produced in the same manner as in Example 1, except that heat curing was not performed when the photoelectric conversion layer was formed.

[0150] <Heat resistance test> A heat resistance test was carried out on the organic photoelectric conversion elements obtained in Example 1 and Comparative Example 1 by holding them at a temperature condition of 200° C. for 50 minutes. The external quantum efficiencies EQE0 and EQE1 of each organic photoelectric conversion element before and after the heat resistance test were measured, and the external quantum efficiency maintenance rate was calculated by the following formula. The results are shown in Table 1. External quantum efficiency maintenance rate = (EQE1 / EQE0) x 100

[0151] [Table 1]

[0152] As is clear from Table 1, the organic photoelectric conversion element of Example 1 exhibits an external quantum efficiency maintenance rate of 89% in a heat resistance test at 200°C, whereas the glass transition temperature Tg of the heat-cured product of the thermosetting component (epoxy resin) constituting the cross-linked structure formed in the photoelectric conversion layer is 160°C. That is, the heat resistance temperature T is 40° C. higher than the Tg of the crosslinked structure in the photoelectric conversion layer, and an efficient thermal curing effect is obtained. In Comparative Example 1, the photoelectric conversion layer was not formed by heating at 200°C to heat-cure the thermosetting component, so the external quantum efficiency before the heat resistance test was high, but the external quantum efficiency after the heat resistance test was significantly reduced, indicating poor heat resistance.

[0153] In addition, a heat resistance test was performed on the organic photoelectric conversion element of Example 1 in the same manner as described above, except that the test temperature was 240°C, and the external quantum efficiency after the heat resistance test was measured. As a result, the external quantum efficiency after the heat resistance test was 10%, and the external quantum efficiency maintenance rate was 22%, which was significantly low, and it was found that the organic photoelectric conversion element of Example 1 did not have heat resistance to 240°C. From the results of this heat resistance test, the heat resistance temperature T of Example 1 is estimated to be 200°C. [Explanation of symbols]

[0154] 10 Organic photoelectric conversion element 11 1st electrode 12 Hole transport layer 13 Photoelectric conversion layer 14 Electron transport layer 15 2nd electrode 20 Organic photoelectric film

Claims

1. An organic photoelectric conversion element having a photoelectric conversion layer including a p-type organic semiconductor and an n-type organic semiconductor, a crosslinked structure made of a heat-cured product of a thermosetting component is formed in the photoelectric conversion layer, The organic photoelectric conversion element has a heat resistance temperature T defined below that is higher than a glass transition temperature Tg of a heat-cured product of the thermosetting component, An organic photoelectric conversion element, wherein the p-type organic semiconductor is a conjugated polymer, and the n-type organic semiconductor is a semiconductor not containing a fullerene skeleton. <Definition of heat resistance temperature T> The external quantum efficiency EQE of the organic photoelectric conversion element was measured after a heat resistance test in which the element was held at a predetermined test temperature for 50 minutes. 1 The value of the external quantum efficiency EQE measured for the organic photoelectric conversion element without performing the heat resistance test. 0 The highest test temperature among the test temperatures in the heat resistance test at which the external quantum efficiency maintenance rate calculated by the following formula using the value of (a) and (b) is 85% or more is defined as the heat resistance temperature T of the organic photoelectric conversion element. External quantum efficiency maintenance rate = (EQE 1 / E.Q.E. 0 ) x 100

2. 2 . The organic photoelectric conversion element according to claim 1 , wherein the heat-resistant temperature T is 100° C. or higher, and the glass transition temperature Tg of the heat-cured product of the thermosetting component is lower than the heat-resistant temperature T by 5° C. or more.

3. 3. The organic photoelectric conversion element according to claim 1, wherein the p-type organic semiconductor is a non-crosslinkable p-type organic semiconductor, and the n-type organic semiconductor is a non-crosslinkable n-type organic semiconductor.

4. The organic photoelectric conversion element according to claim 1 , wherein the thermosetting component contains an epoxy resin as a main component.

5. The organic photoelectric conversion element according to claim 4 , wherein the heat-curable component further comprises a curing agent.

6. 6. The organic photoelectric conversion element according to claim 1, wherein the curing temperature of the thermosetting component is within a range of 100 to 220.degree.

7. The organic photoelectric conversion element according to any one of claims 1 to 6, wherein the n-type organic semiconductor comprises a compound represented by the following formula (I) and / or a polymer of two or more compounds represented by the following formula (I): 【Chemistry 1】 (In the above formula (I), A represents an atom selected from Group 14 of the periodic table, and X 1 ~X 4 R each independently represents a hydrogen atom or a halogen atom. 1a , R 1b each independently represents a linear or branched alkyl group; R 2 ~R 5 each independently represents a linear or branched alkyl group, a linear or branched alkoxy group, a linear or branched thioalkyl group, or a hydrogen atom.

Citation Information

Patent Citations

  • Organic photoelectric conversion element, method for manufacturing the same, and solar cell

    JP2013026483A

  • Organic photoelectric conversion element composition, thin film containing the same, photoelectric cell, organic semiconductor polymer used for the same, compound and method for producing polymer

    JP2013170187A

  • Photoelectric conversion element and solar battery module

    JP2013187501A

  • Photoelectric conversion module and manufacturing method of the same

    JP2014017297A

  • Polythiophene active layer for solar battery

    JP2014170971A